Bio-inspired Corrosion Inhibition of Aluminium Metal in Alkaline Medium - Suma N. D. (Chemical and Materials Sciences - Developments and Innovations Vol. 4, 2024)
The present study proposes to explore the impact of aluminum corrosion in an alkaline medium using an aqueous extract from Cyclea peltata leaves. The conventional approach to corrosion inhibitors has steadily evolved in recent years due to the increased global interest in environmental conservation and the detrimental consequences of chemical use on the ecological balance. Substances that are easily available, renewable, biocompatible, and acceptable to the environment are referred to as green inhibitors or eco-friendly inhibitors. In the present study, pure aluminium strips were used for electrochemical and physicochemical analysis. For experimental purposes, each coupon was cut into 2x3x0.05 cm dimensions. Plant extracts have been proven to be an excellent source for the development of environmentally benign and effective corrosion inhibitors for metals in alkaline medium and research on the topic is ever-increasing. In the present study, aqueous extract of Cyclea peltata leaves extract was used as a corrosion inhibitor for Aluminium coupon in an alkaline medium.